PENINGKATAN KETERAMPILAN MITIGASI BENCANA BAGI GURU DAN SISWA SEKOLAH DASAR DI KECAMATAN POASIA DAN KECAMATAN MANDONGA KOTA KENDARI MELALUI PELATIHAN DAN SIMULASI TANGGAP DARURAT BENCANA - Syawal Kamiluddin Saptaputra; Syefira Salsabila; Akifah Akifah (Anoa : Jurnal Pengabdian Masyarakat Sosial, Politik, Budaya, Hukum, Ekonomi, 2023)
Indonesia is a country that has a high level of natural disaster vulnerability. This geographic situation in Indonesia is what has given rise to the high number of earthquakes in Indonesia. Many of the victims of disasters in several areas occurred in school-aged children both during school hours and outside school hours. This shows that it is important that knowledge about disasters and disaster risk reduction be given from an early age to provide understanding and guidance on the steps that must be taken when they occur. a threat that exists in the surrounding area to reduce the risk of disaster. Mandonga District is one of the sub-districts in Kendari City which is in the highest category (red zone) based on the earthquake risk map. Apart from that, based on the earthquake threat map, Poasia District is in the highest category (red zone). SDN 90 Kendari and SDN 66 Kendari are in the city center and are located in densely populated areas. Based on the facts above, the research team offers community service activities to improve Disaster Mitigation Skills for Elementary School Teachers and Students in Poasia District and Mandonga District, Kendari City through Disaster Emergency Response Training and Simulation. This community service activities take place at SDN 90 Kendari and SDN 66 Kendari. The target of this activity are the students and teachers in schools. Stages of conducting hearings/socialization, collecting data on potential participants, training and simulations, and evaluation. Through this service activity, teachers and students gain additional knowledge and skills regarding disasters